Integration of AHP and GIS to Derive Walkability Index for Women to Access Rail-Transit Stations - Nazri, Nur Intan Marlissa; Naharudin, Nabilah (Department of Urban and Regional Planning, Diponegoro University, 2025)
This study utilized Geographic Information Systems (GIS) and the Analytical Hierarchy Process (AHP) to develop a walkability index for women in accessing rail transit stations. By integrating spatial analysis and multi-criteria decision-making techniques, it addressed key factors such as accessibility, comfort, traffic safety, and attractiveness from a gender-specific perspective. The aim of the research is to identify barriers women face in accessing public transportation and provide actionable insights for urban planning. Expert and public input were gathered to determine the weightage of criteria influencing walkability. Pairwise comparisons through AHP were used to ensure consistent weighting of criteria, while GIS was employed to map and analyze walkability indices. The findings emphasized the need for inclusive urban planning that considers women's unique safety and mobility concerns, offering recommendations for tailored policy interventions. The study demonstrates the effectiveness of GIS and AHP in evaluating walkability, incorporating physical and social dimensions to reflect women’s needs in urban environments. Recommendations include integrating real-time data, engaging diverse groups through surveys and focus groups, and expanding the model to other demographic groups. The research highlights the role of enhanced walkability in promoting mobility, increasing public transit use, reducing congestion, and improving public health. Future studies should refine methodologies, incorporate dynamic data, and broaden assessments to ensure equitable and sustainable urban development. This approach underscores the importance of addressing gender-specific needs to create safer, more accessible, and inclusive cities.